Training process of the medical student in the detection of post-COVID-19 incapacitating sequelae - Rolando Rodríguez Puga (Centro Provincial de Información de Ciencias Médicas, 2023)
Introduction: In the continuous training process of medical students, it is necessary to incorporate current issues; likewise, it is important to know the problems to seek solutions with the science support. Objective: To diagnose the training process of medical students as for the detection of incapacitating sequelae post-COVID-19. Methods: An observational, descriptive and cross-sectional study, with qualitative approach, of 20 students from 5th year of Medicine career, belonging to the University of Medical Sciences in Camagüey was carried out during their stay for the Public Health subject, from July to December, 2022. For such a purpose it was designed and applied an evaluative instrument with dimensions and indicators. Results: It was found that 50.0% of these students were in the age range of 21-26 years, while 65.0% were female. The cognitive dimension was evaluated as bad because 3 indicators, of the 4 that made it up, received that qualification; the same happened with the instrumental dimension. On the other hand, the attitudinal dimension and its 2 indicators were qualified as good. Conclusions: Inadequacies existed in the training process of medical students, which block their professional performance. On the base of the diagnosis, the interest in searching for information related to the detection of post-COVID-19 incapacitating sequelae is confirmed as strength.